2021
DOI: 10.3324/haematol.2020.272559
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum, outcome and management of immune thrombocytopenia associated with myelodysplastic syndromes and chronic myelomonocytic leukemia

Abstract: Myelodysplastic syndromes (MDS) and chronic myelomonocytic leukemia (CMML) are associated with systemic inflammatory or autoimmune diseases in 10-20 % of cases. Among them, immune thrombocytopenia (ITP) has been reported but large studies assessing this association are missing. Whether such patients have a particular phenotype and require particular management is unclear. This study analyzes the clinical spectrum, outcome and therapeutic management of patients with ITP associated with MDS or CMML, in compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…One cerebrovascular accident (CTCAE grade 3) in a responder 22 weeks after starting ROM, one pulmonary embolism (CTCAE grade 4) in a non-responder at seven weeks of ROM and one case of asthenia (CTCAE grade 3) were reported as serious adverse events CTCAE ≥ grade 3 possibly attributed to ROM. This is in line with literature reporting a slightly higher rate of thromboembolic events in patients during TPO-RA treatment compared to patients without TPO-RA [4,16,19,37,38].…”
Section: Safetysupporting
confidence: 92%
See 2 more Smart Citations
“…One cerebrovascular accident (CTCAE grade 3) in a responder 22 weeks after starting ROM, one pulmonary embolism (CTCAE grade 4) in a non-responder at seven weeks of ROM and one case of asthenia (CTCAE grade 3) were reported as serious adverse events CTCAE ≥ grade 3 possibly attributed to ROM. This is in line with literature reporting a slightly higher rate of thromboembolic events in patients during TPO-RA treatment compared to patients without TPO-RA [4,16,19,37,38].…”
Section: Safetysupporting
confidence: 92%
“…Romiplostim (ROM) and Eltrombopag (EPAG) are thrombopoietin receptor agonists (TPO-RA) [15][16][17], which both have already demonstrated clinical efficacy in treating MDS patients with thrombocytopenia [18][19][20][21][22]. Both ROM and EPAG stimulate megakaryocyte differentiation and proliferation [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cohort of 41 MDS/CMML patients with immune thrombocytopenia (ITP), defined by response to steroids, including chronic ITP in 63%, low-risk myelodysplasia in 73% and CMML in 59%, it was recently reported that MDS/CMML-associated ITP have a particular outcome with more severe bleeding and multi-refractory profile than primary ITP, a similar response profile to primary ITP therapy except for intravenous immunoglobulin, and less progression toward acute myeloid leukemia than MDS/CMML without ITP [105].…”
Section: Autoimmune Cytopeniasmentioning
confidence: 99%
“…In particular, recent papers studied patho-biological mechanisms linking ITP and clonal disorders, and their temporal association. Many published experiences focused on ITP and myelodysplastic syndrome (MDS)/chronic myelomonocytic leukemia (CMML), but when analyzing the temporal association, it was evident that, in the majority of cases, ITP followed the diagnosis of MDS/CMML and only very few cases were diagnosed as MDS/CMML after ITP [2][3][4].…”
Section: Introductionmentioning
confidence: 99%